Significant effects of childhood obesity treatment with a web-based component in a randomised controlled study (Web-COP) - Thorén, Annelie; Filipsson, Tobias; Englund, Erling; Sandström, Olof; Janson, Annika; Silfverdal, Sven-Arne (Acta Paediatrica, 2024)
Aim: We evaluated the effect on body mass index standard deviation score (BMI-SDS) of a combined treatment (Web-COP) for children with obesity, including a web-based component targeting their parents. Methods: This randomised controlled trial recruited children 5–12 years of age with obesity (International Obesity Task Force BMI [IOTF-BMI] ≥30 kg/m2) from school health care and outpatient paediatric clinics in in Northern Sweden from 1 June 2019 to 21 June 2020. The children were randomised to Web-COP, an intervention with group sessions and a 12-week web-based component, or standard care. The primary outcome was the change in IOTF BMI-SDS after 6 months. Results: In total, 75 children (33 girls), mean age 9.5 years, were randomised, and 65/75 (87%) children and their parents completed the study, 35/39 (90%) in the Web-COP intervention and 30/36 (83%) in the standard care group. BMI-SDS at 6 months was changed from 3.08 to 2.81 in the intervention group compared to an increase from 3.07 to 3.16 in the standard care group, representing a significant difference between groups (p < 0.001). In the intervention group, 14/30 (47%) reduced their BMI-SDS ≥0.25, compared to none in the standard care group. Conclusion: The parent-focused intervention significantly improved BMI-SDS in children with obesity as compared to children in standard care.